Similar geographic patterns but distinct assembly processes of abundant and rare bacterioplankton communities in river networks of the Taihu Basin. (1st March 2022) - Zhang, Tao; Xu, Sai; Yan, Ruomeng; Wang, Ruyue; Gao, Yuexiang; Kong, Ming; Yi, Qitao; Zhang, Yimin
Highlights: The bacterioplankton community exhibited spatiotemporal dynamics. Abundant and rare bacterioplankton communities showed similar geographic patterns. Abundant and rare bacterioplankton communities had distinct assembly processes. pH and DO were the major factors affecting community structure and assembly process. Abstract: Bacterioplankton play an important role in the biogeochemical cycling in rivers. The dynamics of hydrologic conditions in rivers were believed to affect geographic pattern and assembly process of these microorganisms, which have not been widely investigated. In this study, the geographic pattern and assembly process of bacterioplankton community in river networks of the Taihu Basin were systematically explored using amplicon sequencing of the 16S rRNA gene. The results showed that the diversity, structure, and taxonomic composition of bacterioplankton community all exhibited significant temporal variation during wet, normal, and dry seasons ( p <0.01). The neutral community model and null model were applied to reveal the assembly process of bacterioplankton community. The stochastic process and deterministic process both shaped the bacterioplankton community with greater influence of deterministic process. In addition, the abundant and rare bacterioplankton communities were comparatively analyzed. The abundant and rare bacterioplankton communities exhibited similar temporal dynamics (principal coordinates analysis) and spatial variations (distance-decay relationship), indicating similar geographic patterns. Meanwhile, distinct assembly processes were observed for the abundant and rare bacterioplankton communities. Stochastic process (dispersal limitation) shaped the abundant bacterioplankton community while deterministic process (heterogeneous selection) dominated the assembly process of rare bacterioplankton community. Mantel test, redundancy analysis, and correlation analysis together indicated that pH and dissolved oxygen were the major environmental attributes that affected thestructure and assembly process of bacterioplankton community. These results expanded our understanding of the geographic pattern, assembly process, and driving factors of bacterioplankton community in river networks and provided clues for the underlying mechanisms. Graphical abstract: Image, graphical abstract